Pengaruh Pemberian F 100 Terhadap Perubahan Berat Badan pada Balita Gizi Buruk di Rumah Sakit Bhakti Asih Brebes - Bintanah, Sufiati; Maskhanah, Maskhanah; Nadia, Fika Shafiana; Putri, Sri Hapsari Suhartono (Jurnal Gizi, 2024)
Background: Cases of malnutrition in children under five years old are still a serious problem in Indonesia. The proportion of malnutrition and malnutrition increased from 19.6% to 17.7% in 2015. Brebes Regency ranks first in Central Java and the average number of malnourished  sufferers admitted to hospital is 5 to 8 children under five.Objective: The aim of the research was to determine the effect of administering F100 on changes in body weight in malnourished patients treated at Bhakti Asih Hospital, Brebes. Method: The research design used a quasi-experiment with one group pre and post test. The research location was carried out at Bhakti Asih Hospital, Brebes, from October to December 2020. The research sample was 22 children with malnutrition. Data analysis used the Shapiro Wilk test and paired sample test.  Results: The results of the study showed an increase in body weight of 805 grams. The analysis results show p 0.143 > 0.05. Conclusion: giving F100 can increase body weight in malnourished toddlers but not significantlyKeywords: malnutrition, body weight, formula 100